Ambedkar : India's crusader for human rights - Moore, Kieron (Campfire heroes., 2018)
Presents a graphic novel biography chronicling the life and legacy of Indian leader Bhimrao Ambedkar, an "untouchable" revolutionary who dedicated his life to ending social discrimination and the caste system in India.